Analisis Pengaruh Self-Efficacy terhadap Organizational Citizenship Behaviour dengan Job Satisfaction sebagai Variabel Mediator pada PT. PLN (Persero) Udiklat Jakarta - Dedy Siska Pramono; Denny Taloga (Jurnal Ekonomi Bisnis Indonesia, 2021)
The research objective was to determine the effect of self-efficacy, organizational citizenship behavior, and job satisfaction at PT. PLN (Persero) Udiklat Jakarta. The research method is quantitative. Using secondary and primary data. Data using questionnaires, with 100 respondents. The results of self-efficacy research have a significant effect on organizational citizenship behavior. Self-efficacy has a significant effect on job satisfaction. And then citizenship behavior has a significant effect on job satisfaction. self-efficacy has a significant influence on organizational citizenship behavior through job satisfaction.